2015
DOI: 10.1021/acs.jpclett.5b01345
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Enhanced Electrocatalytic Activity for Oxygen Reduction Reaction on High-Index Platinum n(111)–(111) Surfaces

Abstract: Oxygen reduction reactions (ORRs) on high-index planes of Pt n(111)-(111) were studied by density functional theory (DFT). The stepped surfaces, where n = 2, 3, and 4, showed that O2, O, and OH exhibited higher binding energies along the step compared to the terrace plane. The Pt atoms along the step can become distorted through the binding of the O and OH, where the shift in position of the Pt atoms is the largest along the stepped sites, hence forming stronger bonds with O atoms. One of the two O atoms produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 52 publications
1
29
0
Order By: Relevance
“…34 There is still no overwhelming consensus on the ORR mechanism due to the lack of suitable experimental validation techniques, which can identify accurately the composition and coverage of surface intermediates formed during the reaction. 34,35 To some extent, experimental characterization techniques 27,29,36 and computational catalytic studies 33,37 have been adopted to depict the ORR mechanism and catalyst design in recent years.…”
Section: Orr Theory Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…34 There is still no overwhelming consensus on the ORR mechanism due to the lack of suitable experimental validation techniques, which can identify accurately the composition and coverage of surface intermediates formed during the reaction. 34,35 To some extent, experimental characterization techniques 27,29,36 and computational catalytic studies 33,37 have been adopted to depict the ORR mechanism and catalyst design in recent years.…”
Section: Orr Theory Studiesmentioning
confidence: 99%
“…Yue et al 37 found that the binding energy of O 2 , O, and OH were the highest along the edge of the step. However, the mechanism and binding sites have shown to differ from the non-stepped surface due to the limited positions for certain atoms/molecules to adsorb on.…”
Section: Catalyst Designmentioning
confidence: 99%
“…[73] Furthermore, when the Pt particles have nanosized terraces with ah igh step density like the Pt nanodendrite catalyst, the reactioni ntermediates such as Oa nd OH adsorbed on aP t{100}t erracec an be easily crossovered into av icinal Pt{111}t errace with lower oxygen binding energy and higher ORR activity. However,o ne of the two Oa toms forces the other Oa tom to shift to aw eaker binding site during its protonation, consequently reducingt he energy required for the protonation reaction (O + H + !OH and OH + H + !H 2 O).…”
Section: Resultsmentioning
confidence: 99%
“…However,o ne of the two Oa toms forces the other Oa tom to shift to aw eaker binding site during its protonation, consequently reducingt he energy required for the protonation reaction (O + H + !OH and OH + H + !H 2 O). [73] Furthermore, when the Pt particles have nanosized terraces with ah igh step density like the Pt nanodendrite catalyst, the reactioni ntermediates such as Oa nd OH adsorbed on aP t{100}t erracec an be easily crossovered into av icinal Pt{111}t errace with lower oxygen binding energy and higher ORR activity. [74] Therefore, it is considered that Pt nanodendrites with lots of high-index facets may involve aq uick recovery process of the oxygen-adsorbed Pt sites back to the clean Pt surfaced uring ORR, which may result in the improvement of the catalytic activity.…”
Section: Resultsmentioning
confidence: 99%
“…ref. 53). Recently, it has been suggested that steps at platinum surfaces should likely be blocked by oxygenated species at ''very early'' electrode potentials.…”
Section: Introductionmentioning
confidence: 99%